The relationship between physical activity and anxiety and depressive symptoms among adolescents in 8th to 10th grade primary school in Iceland - Erla Valgerður Birgisdóttir 1994- (2021)
Anxiety and depression disorders are the most common types of mental disorders. Research has established the benefits of physical activity in the reduction of anxiety and depressive symptoms. Parental support plays an important role in promoting good lifestyle choices, such as physical activity, in their children. The aim of this study was to test whether there is an association between physical activity and anxiety and depressive symptoms among adolescents in the 8th–10th grades in primary schools in Iceland. A sample of 2,122, 13 to 15 years old students was drawn out of a large population of pre-collected survey data, 51% females, 48% males and 1% who did not indicate their gender. Results demonstrate that males engage more in physical activity than females, while females reported higher levels of anxiety and depressive symptoms. Overall, results indicated that physical activity significantly reduced anxiety and depressive symptoms among adolescent males and females, while controlling for parental support. Key words: anxiety, depressed mood, physical activity, parental support. Kvíði og þunglyndiseinkenni geta komið fram á marga mismunandi vegu og er ein algengasta tegund geðraskana sem getur haft veruleg áhrif á daglegt líf einstaklinga. Rannsóknir hafa leitt í ljós samband á milli líkamlegrar hreyfingar og umfangs kvíða- og þunglyndiseinkenna. Stuðningur foreldra gegnir stóru hlutverki þegar kemur að hreyfingu barna þeirra. Markmið þessarar rannsóknar var að sjá hvort samband væri á milli hreyfingar og umfangs kvíða- og þunglyndiseinkenna meðal ungmenna í 8. - 10. bekk í grunnskóla á Íslandi. Alls voru 2.122 þátttakendur á aldrinum 13-15 ára valdir af handahófi úr þýðisgögnum Rannsókna & greiningar. Hlutfallsleg skipting eftir kyni var nokkuð jöfn, 1093 stúlkur (51%), 1029 drengir (48%) en tuttugu (1%) greindu ekki frá kyni sínu. Niðurstöður sýndu marktækan mun á tíðni hreyfingar milli kynja og umfangi kvíða- og þunglyndiseinkenna. Á meðan drengir stunduðu meiri hreyfingu, var umfang kvíða- og ...